Depression and its relationship to loneliness and life events among urban poor in the federal territory, Kuala Lumpur, Malaysia - Siti Nor Radhiah Muhammad Yamin,; Nor Ba’yah Abdul Kadir, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study examines the relationship between loneliness, life events and depression among 178 adults in the disadvantage community of Malaysia and to determine predictors of depression. A set of stand-ardized questionnaires was used to measure depression, loneliness and stressful life events. The results showed that loneliness and stressful life events were related to depression. Results also showed that loneliness was a predictor of depression. Implications of the study in terms of theory and practice are also discussed.